Marketing relacji a lojalność klientów - Kałążna-Drewińska, Urszula (Marketing Relations and Customers Loyalty, 2008)
The article includes the following: 1. Characterization of marketing relations as a new concept (idea) relating to business management and its functioning on the market. 2. Qualification of differences in approach to business management: comparison of transaction oriented businesses and businesses focused on forming permanent customer relations. 3. Characterization of loyalty as a result of quality, customer service and value. 4. The results of empirical studies containing problems expressed in points 1, 2, 3.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 33, s. 83-93